Systems Biology of Metabolic and Signaling Networks Energy, Mass and Information Transfer - Aon, Miguel A.; Saks, Valdur; Schlattner, Uwe.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Systems Biology represents a new paradigm aiming at a whole-organism-level understanding of biological phenomena, emphasizing interconnections and functional interrelationships rather than component parts. The study of network properties, and how they control and regulate behavior from the cellular to organism level, constitutes a main focus of Systems Biology. This book addresses from a novel perspective a major unsolved biological problem: understanding how a cell works and what goes wrong in pathology. The task undertaken by the authors is in equal parts conceptual and methodological, integrative and analytical, experimental and theoretical, qualitative and quantitative, didactic and comprehensive. Essentially, they unravel the spatio-temporal unfolding of interacting mass-energy and information networks at the cellular and organ levels, as well as its modulation through activation or repression by signaling networks to produce a certain phenotype or (patho)physiological response. Starting with the historical roots, in thirteen chapters this work explores the Systems Biology of signaling networks, cellular structures and fluxes, organ and microorganism functions. In doing so, it establishes the basis of a 21st century approach to biological complexity.
I Introduction -- From Physiology, Genomes, Systems and Self-Organization to Systems Biology: The Historical Roots of a 21st Century Approach to Complexity -- Systems Biology of Networks: The Riddle and the Challenge -- II Systems Biology of Signaling Networks -- Micrornas and Robustness In Biological Regulatory Networks. A Generic Approach with Applications at Different Levels: Physiologic, Metabolic And Genetic -- Dynamics of Mitochondrial Redox and Energy Networks: Insights from an Experimental-Computational Synergy -- Adenylate Kinase Isoform Network: A Major Hub in Cell Energetics and Metabolic Signaling -- The Control Analysis of Signal Transduction -- III Systems Biology of Cellular Structures and Fluxes -- Moonlighting Function of the Tubulin Cytoskeleton -- Metabolic Dissipative Structures -- Systems Biology Approaches to Cancer Energy Metabolism -- IV Systems Biology of Organ Function -- Network Dynamics in Cardiac Electrophysiology -- Systems Level Regulation of Energy Fluxes via Metabolic Cycles. Role of Creatine and Phosphotransfer Pathways -- V Systems Biology of Microorganisms -- Temporal Partitioning of the Yeast Cellular Network -- Systems Biology and Metabolic Engineering in Bacteria.
Keywords: Life sciences; Proteomics; Biological models; Metabolism; Biology -- Data processing; Life Sciences; Systems Biology; Computer Appl. in Life Sciences; Biological Networks, Systems Biology; Metabolomics; Proteomics; Biophysics and Biological Physics